Hubungan Kepatuhan Protokol Kesehatan Dengan Kejadian Covid-19 Pada Petugas Kesehatan Puskesmas Luragung Di Kabupaten Kuningan - Hayati Mukti Selaras; Andinna Ananda Yusuff; Roheman (LPPM ITEKES Mahardika, 2021)
Medical officers and Health Care workers (or simply health workers) are the most people that impacted by Covid-19. Asymptomatic and pre-symptomatic health workers keep moving to different workplaces and caused to unoptimized health protocols. Proper heatlh protocols in the field is needed because there are still a lot of poor and indecent Personal Protective Equipments (PPE) being used by health workers. This research focused on the correlation of adherence to health protocols with impacted heatlh workers in Puskesmas Luragung, Kuningan. Method used in this study is cross sectional, where the population are all 74 health workers in Puskesmas Luragung. Sample taken are 45 people with questionnaires as the main research’s instrument. The output is bivariate analysis with product momment corellation test. Result in this research showed that almost half of test subjects already have good adherence to health protocols whilst more than 60 % of subjects are exposed to covid-19. The conclusion in this research is the adherence to health protocols have tight corellation to covid-19 case in Puskesmas Luragung, Kuningan. In addition, it is highly recommended to every health workers to implement proper health protocols while serving the health care to patients